The Role of Uremic Intoxication in the Development of Cardiovascular Remodeling in Patients with Chronic Kidney Disease Stages 3a-5d - M. Z. Gasanov; M. N. Kolomyitseva; M. M. Batyushin (Архивъ внутренней медицины)
In recent decades, the prevalence of chronic kidney disease (CKD) in the population has a clear upward trend. This is due, first of all, to an increase in the frequency of occurrence of the main factors leading to its development: diabetes mellitus and arterial hypertension. The progression of CKD against the background of the action of these factors leads to a steady loss of the kidneys of their filtration capacity and the development of complications associated with this process. These include, first of all, metabolic and acid-base disorders, electrolyte abnormalities, uremic intoxication, overhydration, protein-energy wasting, sarcopenia and others. Most of them are involved in the development of endothelial dysfunction and the formation of cardiovascular remodeling (CVR), as a key component of the cardiorenal continuum. At the same time, there is a mutual negative influence of pathology of the cardiovascular system on renal function and manifestations of CKD on cardiovascular hemodynamics. This “vicious circle” leads to the development of end-stage renal disease and an increase in cardiovascular risk and mortality from diseases of the circulatory system in patients with advanced stages of CKD. In this connection, this work is devoted to the study of the role of uremic intoxication and, in particular, indoxyl sulfate, in the development of CVR in patients with CKD at different stages of the disease.